Theoretical and methodological aspects of territorial strategic management concerning socio-ecological and economic development of depressed regions - E. Tyupakov, Konstantin (2020)
The socio-ecological-economic space of the RF regions is positioned as a multifunctional and complex object of strategic management. The effectiveness of the strategic management concerning the regional socio-ecological-economic system directly determines the vector and results of the diverse economic entity activities on the territory, and hence the ways to increase the economic potential of the region, the level of income and life quality of the local population. Effective regulation of economic processes and sustainable development provision of regional systems can be achieved only if all these processes are studied, ie their structure, tendencies, rates have been established; the factors contributing to and hindering development are identified, their fluctuations are diagnosed;